Implementation of Islamic Accounting in Supporting Islamic Economic Principles: A Systematic Literature Review (SLR) - Mahyudin, Mahyudin; Sugianto, Sugianto; Abd Majid, M Shabri (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2025)
This study aims to examine the implementation of Islamic accounting in supporting the principles of Islamic economics through the Systematic Literature Review (SLR) method of 10 SINTA 1 journals indexed by Scopus for the 2019-2024 period. The main focus of this study is to identify the most dominant principles of Islamic economics, evaluate Islamic accounting practices in various sectors, and map challenges and formulate strategic recommendations for strengthening these practices. The results show that the principles of the prohibition of usury, gharar, justice ('adl), transparency, trustworthiness, and profit and loss sharing mechanisms are the main foundations of the Islamic accounting system. The implementation of Islamic accounting is not only limited to Islamic financial institutions, but also extends to the fintech sector, microfinance, agriculture, halal industry, and social finance such as zakat and waqf. However, the integration of sharia values in accounting practices still faces structural and technical challenges, such as incompatibility with conventional accounting standards (IFRS), limited human resources, low sharia literacy, and lack of sharia ESG-based reporting indicators and regulations. This study recommends harmonization of global standards between AAOIFI, Sharia PSAK, and IFRS, provision of fiscal incentives, strengthening the capacity of green-sharia accountants, and integration of Islamic social institutions in the national financial reporting system and SDGs. The findings of this study are expected to provide theoretical and practical contributions in building a fair, transparent, and sustainable Islamic accounting ecosystem in accordance with maqashid al-syari'ah.